Post-weaning growth and profitability of Pelibuey lambs supplemented with three different commercial feedstuffs in Tabasco, Mexico - Hernández-de los Santos, Alma Dorali; Duran-Zamora, Emy Mabiael; Luna-Palomera, Carlos; López-Durán, Saravasti; Vázquez-Martínez, Ignacio Vázquez-Martínez; Muñoz-Osorio, Germani Adrián; Chay-Canul, Alfonso Juventino (Ecosistemas y Recursos Agropecuarios, 2022)
The aim was to evaluate the post-weaning growth of Pelibuey lambs under different types of feeding, considering the cost-benefit ratio (RCB) and profitability. Thirty lambs of 13.14 ± 2.87 kg and 60 days old were used, individual housing, for a period of 49 days. Three feedstuffs were evaluated: Starter (I), Weaning and growing (DyD), and I plus DyD, in a ratio of 50: 50% (I+DyD), with 10 repetitions each. ANOVA was used to evaluate the effect of the type of feeding on daily weight gain (GDP), daily feed consumption (COA), feed conversion (CA) and final weight (PF). Except for CA (P < 0.05), the type of feeding did not significantly affect PF, GDP and COA (P > 0.05). The RCB and profitability were slightly higher with feed I+DyD compared to I and DyD. In conclusion, I+DyD was productive and economically more profitable than I and DyD.